Exploring the factors influencing the cost-effective design of hub-and-spoke and point-to-point networks in maritime transport using a bi-level optimization model - Hoshi Tagawa; Tomoya Kawasaki; Shinya Hanaoka (Asian Journal of Shipping and Logistics (AJSL), 2021)
Hub-and-spoke (HS) networks are cost-effective because they allow the realization of economies of density. However, the cost of point-to-point (PP) networks may be lower than that of HS networks when certain conditions, such as cargo demand, bunker price, vessel size, and the shippers' value of time change. This study explores the factors that influence the cost-effectiveness of HS and PP networks. We developed a mixed-integer programming model that allows for bi-level optimization between shipping lines and shippers. As a case study, we applied it to Chinese and Japanese ports, with both HS and PP networks. We found that high cargo demand increases the use of PP networks while enlarging vessel size increases the use of HS networks. These findings enable us to predict the occurrence of hubbing-shifting from a PP to an HS network - and de-hubbing-shifting from an HS to a PP network.
Keywords: 650; Bi-level optimization; Hub-and-spoke network; Maritime transport; Network design; Point-to-point network